2016
DOI: 10.1080/10428194.2016.1193859
|View full text |Cite
|
Sign up to set email alerts
|

The growing threat of multidrug-resistant Gram-negative infections in patients with hematologic malignancies

Abstract: Prolonged neutropenia and chemotherapy-induced mucositis render patients with hematologic malignancies highly vulnerable to Gram-negative bacteremia. Unfortunately, multidrug-resistant (MDR) Gram-negative bacteria are increasingly encountered globally, and current guidelines for empirical antibiotic coverage in these patients may not adequately treat these bacteria. This expansion of resistance, coupled with traditional culturing techniques requiring 2-4 days for bacterial identification and antimicrobial susc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 110 publications
(142 reference statements)
4
38
0
Order By: Relevance
“…maltophilia is a motile, aerobic, non-fermentative Gram-negative bacillus with the ability to survive on any humid surface, form biofilm and colonize humid surfaces. It is an emerging opportunistic pathogen with multidrug resistance, which particularly affects immunocompromised patients (i.e., with malignances, post-organ transplantation) worldwide [41,42].…”
Section: Cap Caused By Stenotrophomonas Maltophiliamentioning
confidence: 99%
“…maltophilia is a motile, aerobic, non-fermentative Gram-negative bacillus with the ability to survive on any humid surface, form biofilm and colonize humid surfaces. It is an emerging opportunistic pathogen with multidrug resistance, which particularly affects immunocompromised patients (i.e., with malignances, post-organ transplantation) worldwide [41,42].…”
Section: Cap Caused By Stenotrophomonas Maltophiliamentioning
confidence: 99%
“…Gram-negatives, represent the major threat for neutropenic patients because of a bad prognosis in the case of invasive disease. 23,[26][27][28][29][30][31][32][33] Even if the results of the major RCTs and meta-analyses suggest that administration of antibacterial prophylaxis for febrile neutropenia had no impact on the selection of resistant bacteria, it must be remembered that RCTs, and meta-analyses derived from them, should not be used for epidemiological purposes since a RCT generally did not collect data on infections occurring after the end of the study and in patients excluded from the trial itself. 1,34,35 Therefore, no data on patients (and on the environmental ecology) outside the study were available.…”
Section: Does the Prophylaxis Have Adverse Effects?mentioning
confidence: 99%
“…Multi-drug-resistant (MDR) bacteria are becoming increasingly common in patients with hematological malignancies, such as HCT recipients (Baker and Satlin 2016) . It has been previously shown that FMT is capable of reducing antibiotic resistance genes in immunocompetent patients being treated for CDAD (Millan et al 2016) .…”
Section: Discussionmentioning
confidence: 99%